Effect of Minor Reinforcement with Ultrafine Industrial Microsilica Particles and T6 Heat Treatment on Mechanical Properties of Aluminum Matrix Composites - Maxat Abishkenov; Ilgar Tavshanov; Nikita Lutchenko; Kayrosh Nogaev; Daniyar Kalmyrzayev; Assylbek Abdirashit; Nazira Aikenbayeva (Applied Sciences)
This study examines the use of ultrafine (~128 nm) microsilica (composed of a mixture of amorphous and microcrystalline silicon dioxide phases) particles, an industrial waste product, as a reinforcing material to create aluminum matrix composites (AMCs) via ultrasonic-assisted stir casting followed by T6 heat treatment. This study aimed to improve the mechanical properties of pure aluminum, which has insufficient strength for most engineering applications. The main objective of this study is to develop environmentally and economically efficient AMCs with improved properties, namely, the balance between strength and ductility, for further application in caliber rolling processes. Attention is also paid to minor reinforcements using a low concentration of microsilica (~0.36%wt), which minimizes the problems with the wettability of the reinforcing material particles. The composites reinforced with ultrafine microsilica exhibited enhanced mechanical performance, including a 59.7% increase in Vickers microhardness and a significant improvement in tensile strength, reaching 73 MPa. Additionally, T6 heat treatment synergistically improved ductility to 60.3% elongation while maintaining high strength, achieving a balanced performance suitable for forming processes. The study results confirm that using microsilica as a reinforcing material is an effective way to improve the performance of aluminum alloys, while minimizing costs and solving environmental problems.